Full toxicity assessment of Genkwa Flos and the underlying mechanism in nematode Caenorhabditis elegans. - Yan Qiao; Yunli Zhao; Qiuli Wu; Lingmei Sun; Qinli Ruan; Yanyan Chen; Meng Wang; Jinao Duan; Dayong Wang (PLoS ONE, 2014)
Genkwa Flos (GF), the dried flower bud from Daphne genkwa Sieb. et Zucc. (Thymelaeaceae), is a well-known and widely used traditional Chinese medicine. However, we know little about the in vivo mechanism of GF toxicity. Nematode Caenorhabditis elegans has been considered as a useful toxicity assay system by offering a system best suited for asking the in vivo questions. In the present study, we employed the prolonged exposure assay system of C. elegans to perform the full in vivo toxicity assessment of raw-processed GF. Our data show that GF exposure could induce the toxicity on lifespan, development, reproduction, and locomotion behavior. GF exposure not only decreased body length but also induced the formation of abnormal vulva. The decrease in brood size in GF exposed nematodes appeared mainly at day-1 during the development of adult nematodes. The decrease of locomotion behavior in GF exposed nematodes might be due to the damage on development of D-type GABAergic motor neurons. Moreover, we observed the induction of intestinal reactive oxygen species (ROS) production and alteration of expression patterns of genes required for development of apical domain, microvilli, and apical junction of intestine in GF exposed nematodes, implying the possible dysfunction of the primary targeted organ. In addition, GF exposure induced increase in defecation cycle length and deficits in development of AVL and DVB neurons controlling the defecation behavior. Therefore, our study implies the usefulness of C. elegans assay system for toxicity assessment from a certain Chinese medicine or plant extract. The observed toxicity of GF might be the combinational effects of oxidative stress, dysfunction of intestine, and altered defecation behavior in nematodes.